1983
DOI: 10.1029/ja088ia08p06221
|View full text |Cite
|
Sign up to set email alerts
|

Particle and wave dynamics during plasma injections

Abstract: The SCATHA satellite measures particle and wave parameters as it moves outbound on the duskside from the plasmasphere into the plasma sheet. In many cases, plasma waves are not observed in the quiescent plasma sheet prior to a plasma injection. The electron distribution function prior to entry into the plasma sheet is a nearly isotropic soft spectrum, J(E) ∼ 1/E. Just inside the plasma sheet the spectrum begins to harden and becomes anisotropic, J⊥ > J∥. As the satellite penetrates deeper into the plasma sheet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Observations of intense plasma wave turbulence on auroral field lines (Gurnett and Frank, 1977), near the polar cusp (Gurnett and Frank, 1978), and in regions of large-scale Birkeland currents provide the basis for Birketand currents and plasma wave correlative studies. Impulsive bursts observed with wave instruments on the Scatha spacecraft have been interpreted as being the result of spacecraft charging (Koons and Fennel, 1983). To resolve this question, we have examined the spacecraft potential and found that there were no drastic changes in it during the measurements presented here (L. Block, private communication, 1986).…”
Section: Introductionsupporting
confidence: 75%
“…Observations of intense plasma wave turbulence on auroral field lines (Gurnett and Frank, 1977), near the polar cusp (Gurnett and Frank, 1978), and in regions of large-scale Birkeland currents provide the basis for Birketand currents and plasma wave correlative studies. Impulsive bursts observed with wave instruments on the Scatha spacecraft have been interpreted as being the result of spacecraft charging (Koons and Fennel, 1983). To resolve this question, we have examined the spacecraft potential and found that there were no drastic changes in it during the measurements presented here (L. Block, private communication, 1986).…”
Section: Introductionsupporting
confidence: 75%
“…Shaw and Gurnett [1975] reported ECH emissions of 10 mV m -• amplitude that were detected by IMP 6 at radial distances beyond the plasmapause up to 10 R E. The ISEE spacecraft detected ECH waves with amplitudes as large as 1 mV m -• in this region [Gurnett et al, 1979]. Koons and Fennell [1983] emphasized the transient nature of ECH waves by noting that these emissions were detected by SCATHA only during sporadic, highly time dependent particle injection events. This characteristic of the wave emissions is in sharp contrast to the continuous and large-scale spatial nature of the diffuse precipitation.…”
Section: Introductionmentioning
confidence: 98%
“…The space environment is harsh and can adversely affect mission effectiveness through its interaction with spacecraft, components, and materials (Dennison, 2015; Hastings & Garrett, 1996; Lai, 2011). Indeed, environmentally induced anomalies are dominated by spacecraft charging effects (Koons et al, 1999), with the majority related in some way to electrostatic discharge or charging effects (Bedingfield et al, 1996; Leach & Alexander, 1995).…”
Section: Introductionmentioning
confidence: 99%